Adhesion between graphene and polymers: A surface analysis perspective - M. C. F. da Costa; M. R. M. Souza; D. R. G. Larrude; G. J. M. Fechine (eXPRESS Polymer Letters, 2019)
Efficient adhesion between polymers and two-dimensional materials, such as graphene, is fundamental and crucial for the development of flexible devices or special coating materials as well as defining the quality of the transfer processes for these materials. Here, contact angle (CA) measurements of four distinct polymers, low-density polyethylene – LDPE, polypropylene – PP, poly (butylene adipate-co-terephthalate) – PBAT and poly (vinylidene-fluoride-co-trifluoroethylene) – PVDF-TrFE, and graphene achieved by chemical vapor deposition (CVD) were used to understand the adhesion phenomena between such materials. The CA measurements were carried out at specific thermal conditions mimicking a transfer process that is based on direct contact of CVD graphene and polymers above their melting temperature (Direct Dry Transfer – DDT). Surface analysis allowed the efficiency of such transfer method to be pre-estimated owing to an understanding of the adhesion properties of both materials by comparing their polar and dispersive components values. However, rheological properties and chemical structures seemed to be equally important in this evaluation, either by molecular weight modification or introduction of chemical groups onto the surface of polymer films. The results allowed for an understanding of the role of the main factors in adhesion phenomena between graphene and polymers and how they can be used to improve graphene coating during transfer processes.